The Trinity in the gospel of John a thematic commentary on the fourth gospel - Gruenler, Royce Gordon (Grand Rapids, Mi Baker, 1986)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. John -- commentaries; God -- nature of the Trinity -- Bible. N.T. John